The Application Analysis of Hydrocarbons as Refrigerants on Small Commercial Freezers - Zhong Zhifeng; Hu Jiehao; Feng Hui; Li Li; Wu Jianhua (Zhileng xuebao)
Hydrocarbons as one of the natural refrigerants have drawn much attention for their excellent thermophysical properties and environmental performance(ODP=0,GWP is extremely low). This paper compares the operational performances of HCs with several conventional refrigerants, discusses the research progress of the application of HCs on small commercial freezers from the point of theory and tests, and expounds the progress on compressor, lubricating oil and other relevant aspects. Compared to the traditional refrigerant used in small commercial freezers, hydrocarbons have much higher unit mass refrigerating capacity and COP, lower exhaust temperature. Moreover, in actual operation, their cooling rate is faster and noise level is lower. However, hydrocarbons are flammable. Although the refrigerant charge of small commercial freezers is small, relevant fire or explosion experiments should be done when hydrocarbons leak from a small commercial freezer.